1995
DOI: 10.1136/hrt.74.1.53
|View full text |Cite
|
Sign up to set email alerts
|

Concentration dependent cardiotoxicity of terodiline in patients treated for urinary incontinence.

Abstract: Objective-Terodiline, an antimuscarinic and calcium antagonist drug, was used to treat detrusor instability but was withdrawn in 1991 after provoking serious ventricular arrhythmias associated with increases in the corrected QT interval (QTc). This research was performed to relate drug induced electrocardiographic changes in asymptomatic recipients to plasma concentrations of the R( +) and S(-) terodiline enantiomers. (443 (33) and 42 (17) ms'12, paired t tests, P < 0-002 and P < 0 01 respectively) in the 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0
1

Year Published

1997
1997
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 27 publications
1
29
0
1
Order By: Relevance
“…6,13,14 The developability of the terodiline racemate would be viewed differently if only an enantioselective investigation into its toxicity pro®le had been undertaken earlier because, recently, it was shown that although both enantiomers of terodoline are equipotent in their therapeutic bene®ts, the cardiac polarization (prolongation of QTc interval and QRS duration) and proarrhythmic properties were due to the R()-enantiomer. 15 Had this information been available earlier during the clinical development of terodiline, the development of the S(-)-enantiomer instead of the racemate would have been favored.…”
Section: Terodilinementioning
confidence: 98%
“…6,13,14 The developability of the terodiline racemate would be viewed differently if only an enantioselective investigation into its toxicity pro®le had been undertaken earlier because, recently, it was shown that although both enantiomers of terodoline are equipotent in their therapeutic bene®ts, the cardiac polarization (prolongation of QTc interval and QRS duration) and proarrhythmic properties were due to the R()-enantiomer. 15 Had this information been available earlier during the clinical development of terodiline, the development of the S(-)-enantiomer instead of the racemate would have been favored.…”
Section: Terodilinementioning
confidence: 98%
“…The calcium antagonist terodiline has been associated with cardiovascular events, including cardiac arrhythmias with prolonged Q–T intervals [7, 8, 9, 10]. Therefore, in view of the calcium–antagonistic properties of propiverine, the thorough investigation of possible arrhythmogenic effects of propiverine was initiated under a therapeutic dosage regime.…”
Section: Discussionmentioning
confidence: 99%
“…These cardiac arrhythmias were probably caused by the concentration–related prolongation of the frequency–corrected Q–T (Q–Tc) interval [10]. However, this phenomenon has not been reported for anticholinergic drugs, such as oxybutynin [11].…”
Section: Introductionmentioning
confidence: 99%
“…Terodiline. Terodiline concentrations ranging from 32.9 nM up to the clinically relevant level (Thomas et al, 1995) of 120 nM caused statistically significant increases in the mean QT RR1000 of 9 to 12 ms. As in the case of cisapride, the dose-response curve was bell-shaped, with the greatest mean QT prolongation occurring at the third free drug concentration level achieved of 32.9 nM.…”
Section: Qt Prolongation Assessment In the Conscious Dog 829mentioning
confidence: 99%